2003
DOI: 10.1080/08964280309596065
|View full text |Cite
|
Sign up to set email alerts
|

Warm Partner Contact Is Related to Lower Cardiovascular Reactivity

Abstract: The authors investigated the relationship between brief warm social and physical contact among cohabitating couples and blood pressure (BP) reactivity to stress in a sample of healthy adults (66 African American, 117 Caucasian; 74 women, 109 men

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(139 citation statements)
references
References 63 publications
(77 reference statements)
7
126
4
2
Order By: Relevance
“…This would be contrary to human touch, which has demonstrated to be beneficial in a variety of stressful contexts (Grewen et al, 2003;Coan et al, 2006;Ditzen et al, 2007;App et al, 2011). Another possible explanation is that the effects of robot-initiated touch are considerably smaller than those of human touch, and therefore difficult to detect with the sample size of our study.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…This would be contrary to human touch, which has demonstrated to be beneficial in a variety of stressful contexts (Grewen et al, 2003;Coan et al, 2006;Ditzen et al, 2007;App et al, 2011). Another possible explanation is that the effects of robot-initiated touch are considerably smaller than those of human touch, and therefore difficult to detect with the sample size of our study.…”
Section: Discussioncontrasting
confidence: 38%
“…It could be the case that the robot's touch on the shoulder was too limited in contact area and duration. Some literature namely suggests that relatively extensive touching actions such as hugs or massages (contact area) or holding hands (duration) can decrease (physiological) stress responses (e.g., Grewen et al, 2003;Coan et al, 2006;Ditzen et al, 2007). On the other hand, it is claimed that briefly touching one's arm, or providing a supportive pat on the back (e.g., Whitcher and Fisher, 1979;Drescher et al, 1980) can already decrease stress.…”
Section: Stress Responses and Stimuli Aversion (H1 And H2)mentioning
confidence: 99%
See 1 more Smart Citation
“…After the assessment, stress levels were expected to have normalized again. With respect to communication performance, in conformity with the positive effects of a warm contact found earlier (Grewen et al, 2003), psychosocial and affective verbal and non-verbal communication behavior was expected to be associated with less stress responses. Associations may, however, depend on the way the communication is rated as either descriptive or normative.…”
Section: Introductionmentioning
confidence: 56%
“…This indicates the direct link between skin stimulation and physiological processes, a link that is preserved later in life. For instance, gentle stroking touch can lower heart rate and blood pressure (Grewen et al 2003), increase transient sympathetic reflexes and increase pain thresholds (Drescher et al 1980;Uvnäs-Moberg 1997), and affect the secretion of stress hormones (Whitcher and Fisher 1979;Shermer 2004;Ditzen et al 2007). Women holding their partner's hand showed attenuated threat-related brain activity in response to mild electric shocks (Coan et al 2006) and reported less pain in a cold pressor task (Master et al 2009).…”
Section: Touch In Social Communicationmentioning
confidence: 99%